Overview of Psychological Characteristics of Entrepreneurship in Adolescents - Ajeng Hari Mulyani (Publikasi Indonesia, 2022)
The psychological characteristics of adolescents consist of five aspects, namely the capacity aspect, the belief aspect, the consciousness aspect, the motivation aspect and the determination aspect. The aim of this study was to describe the psychological characteristics of entrepreneurship in adolescents. The population in this study were students of SMK Muhammadiyah 1 Pekanbaru with a total sample of 206 students. The research sampling technique used purposive sampling techniques. This study also used a scale of psychological characteristics of entrepreneurship which in total amounts to 31 items. Data were analyzed using CFA analysis test and descriptive analysis test. The results indicated that the aspects of belief and aspects of motivation were dominant in describing the entrepreneurial character of adolescents at SMK Muhammadiyah 1 Pekanbaru City, there was no significant difference between men and women in the desire to be entrepreneurial, and it can be seen that there was already a character of students at SMK Muhammadiyah 1 Pekanbaru City to become entrepreneurs, so it is necessary to be given training to improve the character of entrepreneurship.